Dampak Implementasi Asas Cabotage dan Program Tol Laut Terhadap Ketahanan Wilayah ( Studi di Kabupaten Kepulauan Anambas, Provinsi Kepulauan Riau) - Anwar Sahid; Edy Suandi Hamid; Armaidy Armawi (Universitas Gadjah Mada, 2019)
ABSTRACTSThis study aimed to determined the implementation, constraints and assesed the impact of the cabotage principle and sea toll program on regional resilience in Anambas until the beginning of 2019. Archipelagic districts that had 238 islands in the border region needed ships to supported the development of other sectors and connectivity of disadvantaged, remote, outermost, and border areas (3TP).This study used qualitative descriptive methods in the form of maps, tables and graphs. Data was obtained through observation, in-depth interviews and documentation in Tarempa, Matak Base, sea toll vessels and the Directorate of Sea Traffic and Freight, including literature studies and internet data. The result of this studi showed that cabotage principle succeeded in increasing the number of national commercial fleets fivefold since 2005-2018. The upstream oil and gas company at Anambas complied with cabotage and was not subject to operational disruption.The existence of national ships in Indonesian waters contributed to the aspect of defense security as a source of information. The implementation of the sea toll route to Anambas until the fourth year had not succeeded in reducing the price of goods but maintaining the stock of logistics, especially during extreme weather, supporting food security. Cabotage was important for economies and defense security meanwhile sea tolls contributed to inter-regional connectivity to supported the development of remote, frontier, disadvantaged and borderareas (3TP). Both were encouraging national sea freight to dominated the domestic market share.ABSTRAKPenelitian ini bertujuan untuk mengetahui implementasi, kendala dan mengkaji dampak implementasi asas cabotage dan program tol laut terhadap ketahanan wilayah di Anambas hingga awal tahun 2019. Kabupaten kepulauan yang memiliki 238 pulau di wilayah perbatasan membutuhkankapal untuk menunjang pembangunan sektor lain dan konektivitas daerah tertinggal, terpencil, terluar, dan perbatasan (3TP).Metode yang digunakan adalah deskriptif kualitatif dalam bentuk peta, tabel dan grafik. Data diperoleh melalui observasi, wawancara mendalam dan dokumentasi di Tarempa, Matak Base, kapal tol laut dan Direktorat Lalu Lintas Angkutan Laut dilengkapi studi pustaka dan data internet.Hasil penelitian menunjukkan implementasi asas cabotage berhasil meningkatkan jumlah armada niaga nasional 356 persen pada tahun 2005-2018. Perusahaan hulu migas di Anambas mematuhi cabotage dan tidak terganggu operasionalnya. Keberadaan kapal nasional di perairan Indonesia mendukung aspek pertahanan dan keamanan sebagai salah satu sumber informasi. Implementasi tol laut trayek Anambas hingga awal tahun 2019 belum berhasil menurunkan harga barang tetapi menjaga stok logistik terutama saat cuaca ekstrim, mendukung ketahanan pangan. Cabotage penting bagi perkonomian dan pertahanan keamanan di laut sedangkan tol laut berkontribusi pada konektivitas antarwilayah mendukung pembangunan daerah 3TP. Keduanya mendorong kapal nasional mendominasi angkutan laut dalam negeri.